Black here, black there, black everywhere: using theatre to understand what being-black-in-the-world entailed during apartheid South Africa - Seti, Kitso (Department of Political Studies, 2023)
When a Black person sees a display on stage of a fellow Black person getting killed by a White person, why do they not intervene to stop that killing from happening? One would answer, ‘Because it is just a performance. That Black person is not literally getting killed. It is all an act'. Fair enough. Then why does that spectating Black person get a heavy heart when he sees that killing being portrayed on stage? Is it because it is an experience he is familiar to? He has seen his fellow Blacks getting killed in front of his eyes. What does he do about what he sees on stage? What does the play do to his psyche? Richard Schechner, using Goffman's words, argues that the events on stage must be experienced as, what he deems, ‘actual realization': meaning that “the reality of performance is in the performing” (Bennet, 1997:11). Because the violence taking place on stage is only a performance, the spectator does not intervene as he might in an actual violence he would see taking place outside the theatre hall. However, that does not, as Schechner puts it, make the violence ‘less real' but ‘different real' (Bennet, 1997:11). The imaginary world of theatre is not an entirely ‘unreal' world, it is a world based on real occurrences. These real occurrences are taken to the imaginary world with hopes that when they are returned to the real world they will impact it in different ways, in ways set to transform it.